Термоустойчивость стержневых и пластинчатых элементов конструкций - Конкин, Валерий Николаевич; Лавинский, Владимир Иванович (НТУ "ХПИ", 2005)
The research results of maximum fortunes and steadiness loss of rectilinear bar form and flat form of round plate with calculation of temperature elements materials resiliency module dependence are represented
Keywords: температурное воздействие; огнестойкость элементов строительных конструкций; пожар; линейное расширение